Perlindungan Hukum Wisatawan yang Berkunjung ke Tempat Wisata Berisiko Tinggi di Bali - I Putu Andika Sanjaya; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2022)
The development of tourism opens up many high-risk tourist attractions in Bali. As a tourist place manager, you must pay attention to the comfort, security, safety of tourists, and the arrangement of protection and responsibility in the event of an accident against tourists. This is the background of this research. This research discusses the legal protection for tourists and how the responsibility of the manager of tourist attractions in the event of an accident to tourists. This research uses normative legal research with a statutory approach and legal concept analysis. This research concludes that the legal protection of tourists visiting high-risk tourist attractions in Bali refers to Article 20 of Law Number 10 of 2009 concerning Tourism and Article 4 of Law Number 8 of 1999 concerning Consumer Protection. The manager of tourist attractions must be responsible in the event of an accident referring to Article 1366 of the Civil Code, Article 7 of Law Number 8 of 1999 concerning Consumer Protection, Article 26 of Law Number 10 of 2009 concerning Tourism, and Article 6 number (3) of the Provincial Regulation of Bali Number 5 of 2020 concerning Standards for the Implementation of Balinese Cultural Tourism.